2022
DOI: 10.3892/mmr.2022.12617
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of ATG4A inhibits breast cancer progression and promotes tamoxifen chemosensitivity by suppressing autophagy

Abstract: autophagy-related 4a (aTG4a) is an autophagy regulator. The current study investigated the role of aTG4a in the development of tamoxifen-resistant breast cancer. aTG4a expression was assessed in tumor and adjacent normal tissue obtained from The cancer Genome atlas database. analyses of the disease-free survival between the aTG4a high and low expression groups was then evaluated in patients with breast cancer. cell viability and apoptosis in McF7/r cells was detected using cell counting Kit-8 assay and flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The knockdown of ATG4A levels following 4-hydroxytamoxifen treatment led to increased cell death by apoptosis. Collectively, this study revealed that the knockdown of ATG4A leads to autophagy suppression, and increased the sensitivity of BC cells to 4-hydroxytamoxifen [104]. In our opinion, autophagy genes including BECN1, ULK1 and ATGs influence BC tumourigenic processes, hence could be strategically modulated in a context-dependent manner.…”
Section: The Role Of Autophagy and Autophagy-related Proteins And Pla...mentioning
confidence: 61%
“…The knockdown of ATG4A levels following 4-hydroxytamoxifen treatment led to increased cell death by apoptosis. Collectively, this study revealed that the knockdown of ATG4A leads to autophagy suppression, and increased the sensitivity of BC cells to 4-hydroxytamoxifen [104]. In our opinion, autophagy genes including BECN1, ULK1 and ATGs influence BC tumourigenic processes, hence could be strategically modulated in a context-dependent manner.…”
Section: The Role Of Autophagy and Autophagy-related Proteins And Pla...mentioning
confidence: 61%
“…The aberrant expression of a single DRG has been reported to associate with the therapeutic effects of chemotherapy ( 17 , 53 ), endocrinotherapy ( 54 ) and radiotherapy ( 55 , 56 ). In this study, the prognosis of patients undergoing endocrinotherapy or radiotherapy was worse in the high-risk group than in the low-risk group, possibly owing to treatment resistance induced by degradome dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The studies outlined above demonstrate that in breast cancer, autophagy is not only influenced by tumor-related signaling pathways but also has the capacity to affect the activation status of certain tumor signaling pathways. For example, it was found that the expression of WNT pathway-related proteins was suppressed after the knockdown of ATG4A, a key regulator of cellular autophagy processes [ 60 ]. This suggests that the activation of the WNT pathway seems to have a linkage with autophagy in breast cancer cells as well.…”
Section: Study Of Autophagy and Cancer-related Pathways In Breast Cancermentioning
confidence: 99%